Nutrient Formulation—A Sustainable Approach to Combat PRSV and Enhance Productivity in Papaya - Kavitha Chinnasamy; Naveen Kumar Krishnan; Moganapathi Balasubramaniam; Reena Balamurugan; Pugalendhi Lakshmanan; Kalarani M. Karuppasami; Manoranjitham S. Karuppannan; Elaiyabharathi Thiyagarajan; Senthil Alagarswamy; Saraladevi Muthusamy (Agriculture)
Papaya (Carica papaya L.) is a highly nutritious fruit crop cultivated commercially in the tropical and subtropical regions of the world. Being a shallow rooted fruit crop, it requires frequent application of nutrients. Papaya is highly remunerative due to its high productivity and responds positively to nutrient application. Papaya Ring Spot Virus (PRSV) is a major threat to papaya production, which causes severe yield loss and reduces fruit quality. To combat PRSV and enhance productivity, a nutrient formulation was developed by combining organic, inorganic nutrient sources with biocontrol agents to improve the health and vigor of the plants. Experiments were conducted to standardize the application time and evaluate the efficacy of nutrient formulation in enhancing yield, and to combat papaya ring spot virus (PRSV) incidence in papaya from January 2021 to December 2023 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu, India. The results revealed that foliar application of nutrient formulation at monthly intervals from the 3rd to the 7th month after planting (MAP) along with regular application of recommended dose of fertilizers (RDF) at bimonthly intervals from the 3rd MAP significantly increased the yield (37.79% and 30.57% in TNAU Papaya CO 8 and Red Lady, respectively) and reduced PRSV disease incidence (22.49% in TNAU Papaya CO 8 and 16.53% in Red Lady). Metabolomics study indicates that foliar spray of nutrient formulation enhanced the activators and precursors of defense enzymes, viz., peroxidase (PO), polyphenol oxidase (PPO), phenyl ammonia lyase (PAL), catalase (CAT) and nitrate reductase (NRase) in the sprayed plants over unsprayed control. Therefore, the sprayed plants exhibited tolerance to PRSV incidence by maintaining vigor and induced systemic resistance by the defense enzymes.